The Battle Between Moderate and Fundamentalist Islamic Groups in Covid-19 Memes on Social Media - Asyari, Akhmad; Jumarim, Jumarim; Kadri, Kadri (JURNAL PENELITIAN KEISLAMAN, 2023)
The COVID-19 pandemic not only leaves grief for its survivors but also triggers the netizens to create memes containing religious narratives, especially Islam. This research focuses on uncovering meme narratives about COVID-19 which contain the content of religious thought battles between moderate Islamic groups and fundamentalist Islamic groups. The results show that the COVID-19 global disaster has been used as an arena for fighting as well as promoting the thoughts of moderate Islamic groups versus fundamentalists by using memes as an instrument. The thinking of moderate Islamic groups is represented through COVID-19 memes that are rational and tolerant, while COVID-19 memes containing radical thinking content and blasphemy against certain religions and countries mark the thinking of fundamentalist Islamic groups.